Therapeutic Alternatives in the Management of Late Complications of Surgery for Isolated Coarctation of the Aorta - Tabry, Imad; Rush, Michael (AORTA, 2018)
Despite initial technical success in the treatment of coarctation of aorta, late recurrence and/or development of aneurysms and pseudoaneurysms frequently prompt reintervention. The authors hereby present such a patient whose management required more than a single intervention to treat his complex anatomy, and they discuss the therapeutic alternatives under similar circumstances.
Keywords: graft interposition for repair of coarctation; recurrence of coarctation; development of anastomotic aneurysms and pseudoaneurysms; endovascular stenting for recurrent coarctation; hybrid approach for repair of late complications; ascending to descending aorta bypass grafting through right thoracotomy off-pump